ISOLASI ACTINOMYCETES DARI RIZOSFER TANAMAN OBAT YANG BERPOTENSI MENGHASILKAN ANTIFUNGI TERHADAP Candida albicans RESISTEN FLUCONAZOL - , Iskandar Sobri, S. Farm, Apt., Dr. Ir. Jaka Widada, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
E xploration of new drug compounds based on metabolite compounds produced by microbes increasingly receives high attention. This is due to increasing infection by microbial pathogens that are resistant. In Candida albicans there is also resistance to fluconazole, especially in patients with HIV / AIDS. This study aimed to isolate actinomycetes from the rhizosphere medicinal plants, identify the antifungal activities against C. Albicans r fluconazol and characterize the selected isolates. Actinomycetes isolated from rizosfer of medicinal plants, screening used C. albicans sensitif and fluconazole resistant, characterization of selected isolates including cell morphology and 16S rDNA sequencing. Fermentation with SNB (Starch Nitrate Broth) and extraction to get the antifungal compound, then performed the determination of the active compound with reagent anisaldehid, FeCl3, Lieberman Buchard, Dragendorf, and LC-MS. 37 isolates of actinomycetes are obtained, BDT 5 has the highest activity against Candida albicans r fluconazole. Secondary metabolites contain terpenes and phenolic compounds. With LCMS bioactive compounds suspected as macrolides. Based on phenotypic characters and 16S rDNA sequence analysis, isolates identified as Streptomyces.